Penentuan Koefisien Linier Elektro Optis Pada Aquades dan Air Suling Menggunakan Gelombang RF - Jatwiyono, Lilik Eko; Sugito, Heri; Firdausi, K. Sofjan (BERKALA FISIKA, 2007)
The coefficients of electrooptics for water and refinery water in RF field have been determined. The RF frequency range used in the research is 6,04 MHz to 11 MHz. Two different light beam (532 nm and 632,8 nm) have been used to measure the change of light polarization after transmitted the samples. The result indicates that the linear and quadratic electro optic coefficients appear in the range of frequency-field. The refinery water has greater value of linear electro optic coefficient than aquades. It is also obtained that the greatest change of polarization angle take place when using the green laser in the fieldâ€™s position of upright against the RF frequency field and polarization angle of 900. Â  Keywords: RF field, polarization angle, linear electro optic coefficient.